Manufacturing method of magnetoplumbite type hexagonal ferrite magnetic powder

The method of producing magneto-plumbite-type hexagonal ferrite magnetic powder by adjusting the molar ratio and employing rapid cooling techniques addresses the insufficient radio wave absorption capacity of existing materials in the 60-85 GHz band, achieving enhanced absorption performance.

JP2025038551APending Publication Date: 2025-03-19DOWA ELECTRONICS MATERIALS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023145233
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Existing radio wave absorbers using magneto-plumbite-type hexagonal ferrite magnetic powder may not have sufficient radio wave absorption capacity in the 60-85 GHz band, necessitating the development of a more effective manufacturing method for these materials.

Method used

A method for producing magneto-plumbite-type hexagonal ferrite magnetic powder involves adjusting the molar ratio of Sr, La, Fe, and Al, mixing the powders, granulating, and then sintering the molded articles. The sintered articles are heat-treated at a maximum temperature of 800°C to 1000°C, followed by rapid cooling at an average rate of 14°C or more per minute from the maximum temperature to 200°C, to enhance radio wave absorption properties.

Benefits of technology

The proposed method results in a magneto-plumbite-type hexagonal ferrite magnetic powder with superior radio wave absorption capabilities in the 60-85 GHz band, outperforming conventional materials in terms of absorption capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038551000001
    Figure 2025038551000001
Patent Text Reader

Abstract

To provide a manufacturing method of magnetoplumbite-type hexagonal ferrite magnetic powder suitable for use as a material for radio wave absorbers with excellent radio wave absorption performance in the 60 to 85 GHz band.SOLUTION: Powders that are raw materials for a magnetoplumbite-type hexagonal ferrite magnetic powder containing A, La, Fe, and Al, and having a molar ratio of A, La, Fe, and Al represented by A(1-x)LaxFe(n-y)Aly (A is one or more selected from the group consisting of Sr, Ba, and Ca, and 0.01≤x≤0.7, 1.00≤y≤2.20, 11.00≤n≤12.50), are mixed together, granulated, and molded to obtain a green body, which is then sintered. The sintered body obtained by sintering is then heat-treated at a maximum temperature of 800°C or higher and 1000°C or lower, and then cooled from the maximum temperature of the heat treatment to 200°C at an average cooling rate of 14°C or higher per minute.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to magnetoplumbite-type hexagonal ferrite magnetic powder and a method for producing the same, and more particularly to magnetoplumbite-type hexagonal ferrite magnetic powder suitable for use as a material for radio wave absorbers and the like, and a method for producing the same. [Background technology]

[0002] In recent years, with the advancement of information and communication technology, radio waves in the GHz band are being used for various purposes, such as mobile phones, wireless LAN, satellite broadcasting, intelligent road transport systems, electronic toll collection systems (ETC), and autonomous highway systems (AHS). As the use of radio waves in such high frequency bands becomes more diverse, there are concerns about failures, malfunctions, and malfunctions due to interference between electronic components. As one of the countermeasures, radio wave absorbers are used to absorb unnecessary radio waves and prevent them from being reflected or entering.

[0003] In particular, research into autonomous driving assistance systems has become more active in recent years, and development is underway for in-vehicle radar that uses radio waves (millimeter waves) in the 60 to 85 GHz band to detect information such as the distance between vehicles. As a result, there is a demand for materials that exhibit excellent radio wave absorption capabilities in the 60 to 85 GHz band.

[0004] Materials that exhibit this type of radio wave absorption ability are those that have the general formula A, which shows the atomic ratio of metal elements. (1-x) La x Fe (n-y-z) Al y Co z (wherein A is one or more selected from the group consisting of Sr, Ba, and Ca, and 0.01≦x≦0.70, 1.00≦y≦2.20, 11.00≦n≦12.50, and 0.00≦z≦1.00) has been proposed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication WO2022 / 186060 (Paragraph No. 0008) Summary of the Invention [Problem to be solved by the invention]

[0006] However, as the use of radio waves (millimeter waves) in the 60 to 85 GHz band becomes more diverse in the future, even a radio wave absorber using the magnetoplumbite-type hexagonal ferrite magnetic powder of Patent Document 1 as a material may not have sufficient radio wave absorbing capacity, and there is a demand for a magnetoplumbite-type hexagonal ferrite magnetic powder suitable for use as a material for a radio wave absorber with even better radio wave absorbing capacity.

[0007] Therefore, in view of such conventional problems, the present invention aims to provide a method for producing magnetoplumbite-type hexagonal ferrite magnetic powder suitable for use as a material for a radio wave absorber having excellent radio wave absorption capacity in the 60 to 85 GHz band. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the present inventors have discovered that a ferroelectric material containing A, La, Fe, and Al, and having a molar ratio of A, La, Fe, and Al of A is 0.01 to 0.01. (1-x) La x Fe (n-y) Al y The inventors have found that a magnetoplumbite-type hexagonal ferrite magnetic powder suitable for use as a material for a radio wave absorber having excellent radio wave absorption performance in the 60 to 85 GHz band can be produced by mixing powders that are the raw materials for a magnetoplumbite-type hexagonal ferrite magnetic powder represented by the formula (wherein A is one or more selected from the group consisting of Sr, Ba and Ca, and 0.01≦x≦0.7, 1.00≦y≦2.20, 11.00≦n≦12.50), granulating and molding the powder to obtain a molded body, and then heat-treating the sintered body obtained by this sintering at a maximum temperature of 800°C or more and 1000°C or less, and then cooling from the maximum temperature of this heat treatment to 200°C at an average cooling rate of 14°C or more per minute, thereby completing the present invention.

[0009] That is, the method for producing magnetoplumbite-type hexagonal ferrite magnetic powder according to the present invention comprises the steps of: (1-x) La x Fe (n-y) Al y (wherein A is at least one selected from the group consisting of Sr, Ba and Ca, and 0.01≦x≦0.7, 1.00≦y≦2.20, 11.00≦n≦12.50), powders that are raw materials for a magnetoplumbite-type hexagonal ferrite magnetic powder represented by the formula (1) are mixed, granulated and molded to obtain a green compact, which is then fired, and the fired compact obtained by firing is heat-treated at a maximum temperature of 800°C or more and 1000°C or less, and then cooled from the maximum temperature of the heat treatment to 200°C at an average cooling rate of 14°C or more per minute.

[0010] In this method for producing magnetoplumbite-type hexagonal ferrite magnetic powder, the cooling is preferably performed at an average cooling rate of 16°C or more per minute from the maximum temperature of the heat treatment to 500°C, and the sintering temperature is preferably 1150 to 1400°C. After sintering the compact, the sintered body is preferably pulverized before the heat treatment. The pulverization of the sintered body is preferably performed by coarse pulverization followed by wet pulverization. In addition, when the raw material powder is SrCO 3 Powder and Al 2 O 3 Powder and Fe 2 O 3 Powder and La(OH) 3 Powder and H 3 BO 3 It is preferably in the form of a powder. Effect of the Invention

[0011] According to the present invention, it is possible to provide a method for producing magnetoplumbite-type hexagonal ferrite magnetic powder suitable for use as a material for a radio wave absorber having excellent radio wave absorbing ability in the 60 to 85 GHz band. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In an embodiment of the method for producing magnetoplumbite-type hexagonal ferrite magnetic powder according to the present invention, the powder contains A, La, Fe, and Al, and the molar ratio of A, La, Fe, and Al is A. (1-x) La x Fe (n-y) Al y (wherein A is one or more selected from the group consisting of Sr, Ba and Ca, and 0.01≦x≦0.7, 1.00≦y≦2.20, 11.00≦n≦12.50) powders that are the raw materials for magnetoplumbite-type hexagonal ferrite magnetic powder are mixed, granulated and molded to obtain a green body, which is then sintered. The sintered body obtained by this sintering is then heat-treated at a maximum temperature of 800°C or more and 1000°C or less (preferably 850°C or more and 950°C or less), and then cooled from the maximum temperature of this heat treatment to 200°C at an average cooling rate of 14°C or more per minute.

[0013] By setting the average cooling rate from the maximum temperature of the heat treatment to 200°C at 14°C or more per minute, the material can be used as a radio wave absorber having better radio wave absorption ability in the 60 to 85 GHz band than conventional materials. The average cooling rate from the maximum temperature of the heat treatment to 200°C is preferably 16°C or more per minute, more preferably 17°C or more per minute, and most preferably 18°C ​​or more per minute. In order to further improve the radio wave absorption ability of the radio wave absorber in the 60 to 85 GHz band, the average cooling rate from the maximum temperature of the heat treatment to 200°C is preferably 23°C or more per minute, and more preferably 32°C or more per minute. Such an average cooling rate can be achieved by taking out the fired body into the air at room temperature while still at a high temperature after the heat treatment, but in order to further increase the cooling rate, a screw conveyor equipped with a cooling mechanism may be used. In a screw conveyor equipped with such a cooling mechanism, the screw body has a jacket structure, and the heat-treated sintered body can be cooled at an average cooling rate of 10 to 300°C per minute by conveying the heat-treated sintered body with the screw while flowing cooling water through the jacket. The atmosphere during this cooling is preferably an oxidizing atmosphere, more preferably an air atmosphere, an oxygen atmosphere, a mixed gas atmosphere of oxygen and nitrogen, or a mixed gas atmosphere of oxygen and a rare gas, and most preferably an air atmosphere. Alternatively, cooling may be performed by passing a gas at a temperature lower than the heat treatment temperature.

[0014] Moreover, the above cooling is preferably performed at an average cooling rate of 12° C. or more per minute from the maximum temperature of the heat treatment to 500° C., more preferably at an average cooling rate of 13° C. or more per minute, and most preferably at an average cooling rate of 14° C. or more per minute. In order to further improve the radio wave absorbing ability of the radio wave absorber in the 60 to 85 GHz band, the average cooling rate from the maximum temperature of the heat treatment to 500° C. is preferably 18° C. or more per minute, and more preferably 35° C. or more per minute.

[0015] In the embodiment of the method for producing the magnetoplumbite-type hexagonal ferrite magnetic powder, the sintering temperature is preferably 1150 to 1400°C, more preferably 1200 to 1300°C. After sintering the compact, the sintered body is preferably pulverized before the heat treatment. The pulverization of the sintered body is preferably performed by coarse pulverization followed by wet pulverization. In addition, when the raw material powder is SrCO 3 Powder and Al 2 O 3 Powder and Fe 2 O 3 Powder and La(OH) 3 Powder and H 3 BO 3 It is preferably in the form of a powder. EXAMPLES

[0016] Hereinafter, examples of the method for producing magnetoplumbite-type hexagonal ferrite magnetic powder according to the present invention will be described in detail.

[0017] [Example 1] First, 380 g of SrCO 3 Powder (purity 99% by mass) and 346 g of Al 2 O 3 Powder (purity 99.9 mass%) and 2981 g of Fe 2 O 3 Powder (purity 99% by mass) and 277 g of La(OH) 3 Powder (purity 99.99% by mass) and 16 g of H 3 BO 3The powder was weighed. The molar ratio of Sr, La, Fe, and Al in this raw material powder was Sr:La:Fe:Al=0.64:0.36:9.22:1.69. After mixing this raw material powder with a Henschel mixer, it was further mixed by a dry method with a vibration mill. The mixed powder thus obtained was granulated into pellets to obtain a 2 kg molded body, which was then filled into a sintering sheath (sintering container), and this sintering sheath was placed in a box-type sintering furnace and sintered at 1260 ° C. for 4 hours in the air. The sintered body obtained by this sintering was coarsely ground with a hammer mill, and the obtained coarse powder was wet-ground with an attritor for 70 minutes (using water as a solvent), the obtained slurry was subjected to solid-liquid separation, and the obtained cake was dried and crushed. The crushed powder thus obtained was loaded into an alumina boat, which was then placed in a tubular furnace. While maintaining the inside of the tubular furnace in an air atmosphere, the temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and heat-treated by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder. The alumina boat was then removed from the tubular furnace into the air at room temperature over 5 seconds, and the heat-treated powder was cooled to obtain a magnetic powder. During this heat treatment, the temperature of the powder was measured using a thermocouple placed in the powder packed in the alumina boat, and the time it took for the heat-treated powder in the alumina boat removed from the tubular furnace to cool was measured.The time it took to cool from 900°C, the maximum heat treatment temperature, to 200°C was 19 minutes, and the time it took to cool from 900°C to 500°C was 9 minutes.The average cooling rate when cooling from 900°C to 200°C was 37°C / min, and the average cooling rate when cooling from 900°C to 500°C was 44°C / min.

[0018] The magnetic powder thus obtained was subjected to composition analysis and X-ray diffraction (XRD) measurement. In the composition analysis of the magnetic powder, the quantification of Sr, La, Fe and Al was performed using a high-frequency induction plasma emission spectrometer ICP (720-ES) manufactured by Agilent Technologies Inc. As a result, the molar ratio of Sr, La, Fe and Al in the magnetic powder was Sr:La:Fe:Al = 0.64:0.36:9.50:1.65. In addition, 370 ppm of B was detected in the magnetic powder. The X-ray diffraction measurement of the magnetic powder was performed by powder X-ray diffraction method (XRD) using a powder X-ray diffractometer (horizontal multipurpose X-ray diffractometer Ultima IV manufactured by Rigaku Corporation) with a CuKα ray source, a tube voltage of 40 kV, a tube current of 40 mA, and a measurement range of 2θ = 10 ° to 75 °. As a result of the X-ray diffraction measurement, it was confirmed that the magnetic powder obtained was a magnetoplumbite-type hexagonal ferrite, and no crystal phase other than magnetoplumbite-type crystals was confirmed. From the result of composition analysis, the obtained magnetoplumbite-type hexagonal ferrite contained Sr, La, Fe, and Al, and the molar ratio of Sr, La, Fe, and Al was Sr. (1-x) La x Fe (n-y) Al y It can be expressed as (x=0.36, y=1.65, n=11.15).

[0019] In addition, 0.36 g of the magnetic powder obtained and 0.84 g of microcrystalline cellulose were mixed to obtain a mixed powder, which was pressed at 151 MPa to obtain a compact with a diameter of 13 mm and a thickness of 5.5 mm. This compact (sample) was placed on a sample holder (diameter φ10 mm) of a terahertz spectroscopy system (TAS7400SL manufactured by Advantest Corporation), and the transmission attenuation was measured by terahertz wave time domain spectroscopy with the measurement mode being transmission, the frequency resolution being 1.9 GHz, the vertical axis being absorption, the horizontal axis being frequency (THz), and the cumulative number being 2048. At the same time, the transmission attenuation of the blank was measured by the same method without placing the sample on the sample holder, and the measured signal waveform of the sample and the reference waveform of the blank were expanded to 8448 ps and Fourier transformed, and the Fourier spectrum ratio (Ssig / Sref) (Ssig is the amplitude of the Fourier spectrum of the sample, and Sref is the amplitude of the Fourier spectrum of the blank) was obtained, and the transmission attenuation of the compact (sample) was calculated. As a result, the transmission attenuation of the compact at a frequency of 76 GHz was 6.3 dB.

[0020] [Example 2] The temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and a heat treatment was performed by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder.The heating of the alumina boat in the tubular furnace was then stopped, and the temperature of the heat-treated powder was cooled from 900°C to 700°C.The alumina boat was then removed from the tubular furnace into the air at room temperature for 5 seconds to cool the heat-treated powder.A magnetic powder was obtained in the same manner as in Example 1, except for this. In addition, using a method similar to that of Example 1, the temperature of the powder was measured using a thermocouple placed in the powder filled in the alumina boat, and the time until the heat-treated powder in the alumina boat removed from the tubular furnace was cooled was measured.The results showed that it took 8 minutes to cool from 900°C, the maximum heat treatment temperature, to 700°C, 6 minutes to cool from 700°C to 500°C, and 10 minutes to cool from 500°C to 200°C, and the average cooling rate when cooling from 900°C to 200°C was 29°C / min, and the average cooling rate when cooling from 900°C to 500°C was 29°C / min.

[0021] For the magnetic powder thus obtained, the transmission attenuation of the compact (sample) was calculated by the same method as in Example 1, and the transmission attenuation of the compact at a frequency of 76 GHz was 5.8 dB.

[0022] [Example 3] The temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and a heat treatment was performed by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder.The heating of the alumina boat in the tubular furnace was then stopped, and the temperature of the heat-treated powder was cooled from 900°C to 500°C.The alumina boat was then removed from the tubular furnace into the air at room temperature for 5 seconds to cool the heat-treated powder.A magnetic powder was obtained in the same manner as in Example 1, except for this. In addition, using a method similar to that used in Example 1, the temperature of the powder was measured using a thermocouple placed in the powder filled in the alumina boat, and the time required for the heat-treated powder in the alumina boat removed from the tubular furnace to cool was measured.The time required for the powder to cool from the maximum heat treatment temperature of 900°C to 500°C was 29 minutes, and the time required for the powder to cool from 500°C to 200°C was 10 minutes.The average cooling rate when cooling from 900°C to 200°C was 18°C / min, and the average cooling rate when cooling from 900°C to 500°C was 14°C / min.

[0023] For the magnetic powder thus obtained, the transmission attenuation of the compact (sample) was calculated by the same method as in Example 1, and the transmission attenuation of the compact at a frequency of 76 GHz was 4.8 dB.

[0024] [Comparative Example 1] The temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and a heat treatment was performed by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder.After that, the heating of the alumina boat in the tubular furnace was stopped and the temperature of the heat-treated powder was cooled from 900°C to 300°C.The alumina boat was then removed from the tubular furnace into the air at room temperature for 5 seconds to cool the heat-treated powder.A magnetic powder was obtained in the same manner as in Example 1, except for this. In addition, using a method similar to that of Example 1, the temperature of the powder was measured using a thermocouple placed in the powder filled in the alumina boat, and the time until the heat-treated powder in the alumina boat removed from the tubular furnace was cooled was measured.The results showed that it took 29 minutes to cool from 900°C, the maximum heat treatment temperature, to 500°C, 25 minutes to cool from 500°C to 300°C, and 6 minutes to cool from 300°C to 200°C, and the average cooling rate when cooling from 900°C to 200°C was 12°C / min, and the average cooling rate when cooling from 900°C to 500°C was 14°C / min.

[0025] For the magnetic powder thus obtained, the transmission attenuation of the green compact (sample) was calculated by the same method as in Example 1, and the transmission attenuation of the green compact at a frequency of 76 GHz was 4.0 dB.

[0026] [Comparative Example 2] The temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and heat-treated by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder.The heating of the alumina boat in the tubular furnace was then stopped, and the temperature of the heat-treated powder was cooled from 900°C to 200°C.The alumina boat was then removed from the tubular furnace into the air at room temperature for 5 seconds to cool the heat-treated powder.A magnetic powder was obtained in the same manner as in Example 1, except for this. In addition, using a method similar to that of Example 1, the temperature of the powder was measured using a thermocouple placed in the powder filled in the alumina boat, and the time until the heat-treated powder in the alumina boat removed from the tubular furnace was cooled was measured.The time until the powder was cooled from the maximum heat treatment temperature of 900°C to 500°C was 29 minutes, and the time until the powder was cooled from 500°C to 200°C was 50 minutes.The average cooling rate when cooling from 900°C to 200°C was 8.9°C / min, and the average cooling rate when cooling from 900°C to 500°C was 14°C / min.

[0027] For the magnetic powder thus obtained, the transmission attenuation of the compact (sample) was calculated by the same method as in Example 1, and the transmission attenuation of the compact at a frequency of 76 GHz was 4.0 dB.

[0028] [Comparative Example 3] The temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and a heat treatment was performed by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder.The tubular furnace was then cooled so that the temperature of the heat-treated powder was reduced from 900°C to 200°C at a rate of 1.5°C / min, and the alumina boat was then removed from the tubular furnace into the air at room temperature in 5 seconds.A magnetic powder was obtained in the same manner as in Example 1, except for this.

[0029] For the magnetic powder thus obtained, the transmission attenuation of the compact (sample) was calculated by the same method as in Example 1, and the transmission attenuation of the compact at a frequency of 76 Hz was 3.5 dB.

[0030] [Comparative Example 4] The temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and a heat treatment was performed by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder.The tubular furnace was then cooled so that the temperature of the heat-treated powder was reduced from 900°C to 200°C at a rate of 0.7°C / min, and the alumina boat was then removed from the tubular furnace into the air at room temperature over a period of 5 seconds.A magnetic powder was obtained in the same manner as in Example 1, except for this.

[0031] For the magnetic powder thus obtained, the transmission attenuation of the compact (sample) was calculated by the same method as in Example 1, and the transmission attenuation of the compact at a frequency of 76 GHz was 3.2 dB.

[0032] [Comparative Example 5] The temperature of the alumina boat in the tubular furnace was raised from room temperature to 900°C at a heating rate of 200°C / min, and heat treatment was performed by holding at this temperature (900°C) for 20 minutes to obtain a heat-treated powder.The tubular furnace was then cooled so that the temperature of the heat-treated powder was reduced from 900°C to 200°C at a rate of 0.2 / min, and the alumina boat was then removed from the tubular furnace into the air at room temperature over 5 seconds.A magnetic powder was obtained in the same manner as in Example 1, except for this.

[0033] For the magnetic powder thus obtained, the transmission attenuation of the compact (sample) was calculated by the same method as in Example 1, and the transmission attenuation of the compact at a frequency of 76 GHz was 3.2 dB.

[0034] Table 1 shows the production conditions and properties of the magnetic powders obtained in these Examples and Comparative Examples, and the properties of the green compacts.

[0035] [Table 1] [Industrial Applicability]

[0036] The magnetoplumbite-type hexagonal ferrite magnetic powder according to the present invention can be used to produce a radio wave absorber sheet that has excellent radio wave absorbing ability in the 60 to 85 GHz band.

Claims

1. A, La, Fe, and Al are contained, and the molar ratio of A, La, Fe, and Al is A (1-x) La x Fe (n-y) A y (wherein A is at least one selected from the group consisting of Sr, Ba and Ca, and 0.01≦x≦0.7, 1.00≦y≦2.20, 11.00≦n≦12.50), a powder serving as a raw material for the magnetoplumbite type hexagonal ferrite magnetic powder is mixed, the powder is granulated and molded to obtain a molded body, the molded body obtained by the sintering is heat-treated at a maximum temperature of 800°C or more and 1000°C or less, and then cooled from the maximum temperature of the heat treatment to 200°C at an average cooling rate of 14°C or more per minute.

2. 2. The method for producing magnetoplumbite-type hexagonal ferrite magnetic powder according to claim 1, wherein the cooling is performed from the maximum temperature of the heat treatment to 500° C. at an average cooling rate of 16° C. or more per minute.

3. The method for producing magnetoplumbite type hexagonal ferrite magnetic powder according to claim 1 or 2, characterized in that the sintering temperature is 1150 to 1400°C.

4. 3. The method for producing magnetoplumbite-type hexagonal ferrite magnetic powder according to claim 1, wherein the sintered body is pulverized after the compact is sintered and before the heat treatment is performed.

5. 5. The method for producing magnetoplumbite hexagonal ferrite magnetic powder according to claim 4, wherein the pulverization of the sintered body is carried out by coarse pulverization followed by wet pulverization.

6. The raw material powder is SrCO 3 Powder and Al 2 O 3 Powder and Fe 2 O 3 powder and La(OH) 3 Powder and H 3 B.O. 3 3. The method for producing magnetoplumbite-type hexagonal ferrite magnetic powder according to claim 1, wherein the magnetic powder is a powder.

Citation Information

Patent Citations

  • Magnetic powder of magnetoplumbite-type hexagonal ferrite and method for producing same, and radio wave absorber and method for producing same

    WO2022186060A1